Differences in epileptic symptoms depending on the type of autoimmune-mediated limbic encephalitis. (August 2015) - Lin, Qingxia; Wang, Xuefeng
Abstract : Limbic encephalitis (LE) is an inflammatory disease of the central nervous system that is characterized by the selective involvement of limbic structures. The clinical manifestations of LE include the acute or sub-acute onset of recent memory disorders, mental disorders and seizures. Autoimmune-mediated LE is a major type of non-infectious LE; seizure is a hallmark of this type of LE. The treatment of epilepsy, which is a key factor that affects the prognosis of LE patients, warrants special attention. Understanding the characteristics of epilepsy caused by autoimmune-mediated LE and providing the appropriate treatment will help to improve patients' outcomes. In this article, we extensively review the literature related to autoimmune-mediated LE epidemiology, mechanisms, characteristics and seizure frequency and onset, and we discuss the possible diagnosis and treatment of this disease.